2017
DOI: 10.36834/cmej.36683
|View full text |Cite
|
Sign up to set email alerts
|

The emotional intelligence of pediatric residents – a descriptive cross-sectional study

Abstract: Background: Emotional Intelligence (EI) is a type of social intelligence.  Excellent scores are achieved by displaying high levels of empathy in interpersonal relationships, strong skills in managing stressful situations as well as other personal competencies. Many of the social competencies that EI describes may have a direct impact on patient care. The objective of this study was to describe EI of pediatric residents and to identify if there are EI skills that should be selected for targeted intervention.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Emotional intelligence (EI) may be understood as certain traits of personality that are revealed trough the individual's self-reflection and that influence the ability to cope with environmental requirements and pressure ( Bar-On, 1997;Ekman & Friesen, 2013). In foreign countries, a tendency is observed that medical residents are distinguished with average or above average EI as compared to the general population (McLeod & Sonnenberg, 2017). We could not find literature about what EI expression is characteristic for young Lithuanian doctors when they start work.…”
mentioning
confidence: 70%
“…Emotional intelligence (EI) may be understood as certain traits of personality that are revealed trough the individual's self-reflection and that influence the ability to cope with environmental requirements and pressure ( Bar-On, 1997;Ekman & Friesen, 2013). In foreign countries, a tendency is observed that medical residents are distinguished with average or above average EI as compared to the general population (McLeod & Sonnenberg, 2017). We could not find literature about what EI expression is characteristic for young Lithuanian doctors when they start work.…”
mentioning
confidence: 70%
“…Consider psychometric tools such as the EQ-i (McLeod and Sonnenberg, 2017), character-based training from the Ivey Business School (Sultan et al , 2019) or Myers Briggs Type Indicator (Ramachandran et al , 2020) to kick start this endeavor. Reflection can be facilitated through faculty mentor and/or peer feedback, using observation with coaching feedback.…”
Section: The Results: Making Leadership Development Letter-perfectmentioning
confidence: 99%
“…The available studies on EI among health care providers are on their burnout, job performance, and caring behaviour of nurses, and medical educators. [9][10][11][12][13][14] Analysis of data with regard to EI dimensions and age and gender of the medical interns has shown interesting observations. The EQ in the 21 years age category was lower than all other age groups.…”
Section: Discussionmentioning
confidence: 99%